Analysis of a European cupboard by XRF, Raman and FT-IR. (October 2018) - Felix, Valter S.; Mello, Ulisses L.; Pereira, Marcelo O.; Oliveira, Ana L.; Ferreira, Douglas S.; Carvalho, Cristiano S.; Silva, Fabricio L.; Pimenta, André R.; Diniz, Marilia Garcia; Freitas, Renato P.
Abstract: In this paper, a European black Japanned piece of furniture (dated to approximately 1860) was analyzed by XRF, Raman spectroscopy and FT-IR techniques. The analyses detected pigments such as vermilion/cinnabar [HgS], Massicot [PbO], lamp black [C] and green earth [K[(Al, Fe III ), (Fe II, Mg)](AlSi3, Si4 )O10 (OH)2 ], which were possibly dissolved in gum arabic. The analyses also determined that the metallic ornaments consist of a brass alloy with traces of gold and that gold was also used in some golden regions of the polychrome. The results obtained assisted restorers in choosing suitable intervening procedures and contributed to a better understanding of the cupboard manufacturing process. Highlights: Analysis of black Japanned by XRF. Analysis of black Japanned by Raman Spectroscopy. Analysis of black Japanned by FT-IR.